Trapped in a Cylinder - Hwozdek, Jenny (Homœopathic Links, 2013)
This case expanded my knowledge of a small remedy that I had never used. In fact, I was only familiar with its application as an acute. Using the schema of Dr. Roger Morrisonʼs book, “Carbon: Organic and Hydrocarbon Remedies in Homeopathy”, I was able to arrive at this remedy through a systematic thought process that led me through the maze of potential Carbon compounds. The rewards of the journey have been a healthier client, and a deeper understanding of this compound remedy as a reflection of the elements that make up its composition.
Keywords: Carbons; Gunpowder